Identifikasi penggunaan kata tidak baku pada merek dagang toko dan jasa di kota bengkulu - Tri Dina Ariyanti; Triesna Fuji Hatma (BAHASTRA, 2020)
The purpose of this research is to describe non-standard words in trademark brands and services in Bengkulu city. The method used in this research is descriptive. Descriptive method in this study was used to get the description of writing non-standard words in the trademark of shops and services in Bengkulu city. Some non-standard word writing obtained by the author has become a sample in this study including writing the words â€œphoto copyâ€, â€œantriâ€, â€œbisâ€. The discussion above found that the writing of non-standard words still exists in public places, therefore, it impacts on the community, especially students, educators, and others. The conclusion of the research is that the writing of non-standard words still exists in public places, so that it impacts the community, especially students, educative leaders, and others. The conclusions of the research based on the theory of incompetence are marked by deviations including: use of words, spelling, and sentence structure. Based on the results of research obtained and associated with the theory of non-standardization obtained in the form of words and spelling. This can be seen from the shop owners and their trademark writing services that are not based on standard words that have been set with the PEUBI standard (Indonesian Spelling Guidelines). The results of this study found that the writing of non-standard words still exist in public places, so that the impact on the community, especially students, students, educators, and others is that writing non-standard words still exist in public places, so that the impact on society especially students, students, educators, and others.